Rethinking of the relationship between agriculture and the “urban” economy in Beijing: an input-output approach - Yang, Zhenshan; Cai, Jianming; Dunford, Michael; Webster, Douglas (Technological and Economic Development of Economy, 2014)
Despite the irresistible drive of urban growth, the questions as to whether and how agriculture is restructured and repositioned in relation to urban development have received little attention. Based on the method of hypothetical extraction from input-output tables, and on the Beijing case, this paper puts forward an approach to assess the dependence of the agro-economy on urban sectors. The research shows that in Beijing in the period from 1982 to 2007 the relationship between agriculture and the urban economy has gone through three phases. At the start of the economic reform, the relationship was weak, characterised by intensive inputs of agricultural productive materials and policy orders. What followed was a phase of disconnection characterised by fast urban growth and low competitive status of agriculture. The third was a period of increasingly integrated development with technological inputs and upgrading of the management of agriculture. The current strong relationship indicates that agriculture can be tuned to meet the preferences of urban consumers. Key associated urban sectors are screened out to verify this relationship. The approach is valuable for quantifying the structural relationship between agriculture and urban sectors, for further analysing rural-urban economic relationships to support development policy design and programming. First published online: 28 Jan 2014